DEBT AND INVESTMENT POLICY TOWARDS ISLAMIC ECONOMIC DEVELOPMENT - zulaikha; Salma Wahida (Assets Journal: Journal of Economic and Business, 2026)
The purpose of this study is to examine debt and investment policies on Islamic economic development. In this study, the author uses a descriptive research method which explains in detail the debt and investment policies in Islamic economic development. Meanwhile, to analyze the data using content analysis, which is a method used to draw conclusions from a text. The results of this study indicate that debt can be a pillar of economic development. However, debt is the last alternative used.